Synthesis of Dihydrospiro Furo[2,3-c]pyrazoles Promoted by Hypervalent Iodine in Water - Kale, Ashok; Medishetti, Nagaraju; Bingi, Chiranjeevi; Atmakur, Krishnaiah (Synlett, 2018)
A simple, green protocol has been accomplished for the synthesis of dihydrospirofuro[2,3-c]pyrazoles in aqueous medium involving pyrazolone and aldehydes in a one-pot reaction promoted by bis(acetoxy)iodobenzene (BAIB) at ambient temperature. The protocol presented herein describes a new transformation where two molecules of pyrazolone react with an aldehyde in a Knoevenagel condensation followed by a Michael addition, and the resulting dienol was rearranged to the title compound. High compatibility, easy work-up, and excellent yields are the advantages of this protocol.
Keywords: benzaldehydes; pyrazolones; bis(acetoxy)iodobenzene